Qality of group decision making of students in high and elementary schools from the perspective of teachers - Pljakić, Goran (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2021)
In this paper, the author investigates how teachers perceive the quality of decision - making of students of different ages while working in small groups. The examination of the beliefs of 162 teachers about the quality of decisions that students make while working in small groups was achieved by the KDO-MG scale, which was created and tested for the purposes of this research. A two-factor univariate analysis of variance found that there was a statistically significant difference between the beliefs of teachers, subject teachers and high school teachers about the quality of students’ decision-making during work in small groups. The difference is reflected in the fact that teachers’ beliefs indicate that the quality of decisions is higher among high school students than is the case with elementary school students.